Associations of accelerometer-measured sedentary time, sedentary bouts, and physical activity with adiposity and fitness in children. Issue 1 (2nd January 2020) - Jones, Melissa A.; Skidmore, Paula Ml; Stoner, Lee; Harrex, Harriet; Saeedi, Pouya; Black, Katherine; Barone Gibbs, Bethany
ABSTRACT: Sedentary time (ST) has been inconsistently associated with adiposity and cardiorespiratory fitness in children in previous studies. We studied cross-sectional associations of ST, light physical activity (LPA), and moderate-to-vigorous physical activity (MVPA) with fat mass index (FMI) and cardiorespiratory fitness (estimated VO2 max). Associations were evaluated with and without considering pattern of ST by bout length. We measured ST and activity by a wrist-worn accelerometer, FMI by bioelectrical impedance, and VO2 max by Pacer test in 443 children (51.2% girls, 10.2 ± 0.6 years). Isotemporal substitution regression models estimated the effects of substituting ST, LPA, and MVPA on FMI and VO2 max. Further models repeated analyses separating ST into short (<10 min) and long (≥10 min) bouts. Only replacing ST or LPA with MVPA was consistently associated with lower FMI and greater VO2 max. When separated by bout length, only one unique association was found where replacing long ST bouts with short ST bouts was associated with lower FMI in girls only. In conclusion, activity pattern is associated with adiposity in girls and fitness in boys and girls. Separating ST into long and short ST bouts may be of minimal importance when assessing associations with adiposity and fitness using wrist-worn accelerometry in children.